2010
DOI: 10.3208/sandf.50.623
|View full text |Cite
|
Sign up to set email alerts
|

Burial Consolidation Processes of Deep-Sea Sediments: An Example of Core Sediments Collected from the Labrador Sea in the Northwest Atlantic

Abstract: Progressive change of microfabrics of deep-sea sediments during early diagenesis was analyzed using two drill cores collected from the Sites U1305 and U1306 of the Integrated Ocean Drilling Program Expedition 303 in the Labrador Sea in the northwest Atlantic Ocean. Microfabrics were analyzed by scanning electron microscope and deduced from anisotropy of magnetic susceptibility. DiŠerent microfabrics in three layers were distinguished in both cores: Surface layer with general void ratio À2.5, subjacent layer wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…5). Previous studies have reported clay microaggregates in soils and continental margin sediments (e.g., Edwards and Bremner 1967;Ransom et al 1997Ransom et al , 1998Kawamura 2010;Nishida et al 2013). The present observation of clay microaggregates in pelagic sediments indicates that such microstructure is a common characteristic of clay in various environmental sediments.…”
Section: Implications For Clay Microstructuresmentioning
confidence: 97%
See 3 more Smart Citations
“…5). Previous studies have reported clay microaggregates in soils and continental margin sediments (e.g., Edwards and Bremner 1967;Ransom et al 1997Ransom et al , 1998Kawamura 2010;Nishida et al 2013). The present observation of clay microaggregates in pelagic sediments indicates that such microstructure is a common characteristic of clay in various environmental sediments.…”
Section: Implications For Clay Microstructuresmentioning
confidence: 97%
“…Sample prep for microstructure observation 472 t-Butyl alcohol freeze-drying method t-Butyl alcohol freeze-drying was performed according to previously reported procedures (Takizawa et al 1995;Kawamura and Ogawa 2004;Kawamura 2010;Nishida et al 2013). The tiny agarose-embedded sample plugs allow rapid sample processing for subsequent fluid displacement.…”
Section: Uramoto Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…The microfabric anisotropy of phyllosilicate-rich sediments generally increases during burial and progressive compaction in marine environments (e.g., Bennett & Hulbert, 1986;Day-Stirrat et al, 2012;Ho et al, 1999), of course, also depending on mineral composition and distribution (e.g., Sintubin, 1994). This can be determined indirectly by, for example, AMS (anisotropy of the magnetic susceptibility) measurements, void ratios, or preferred alignment of larger grains, for example, illite flakes (e.g., Agar et al, 1989;Bowles et al, 1969;Kawamura & Ogawa, 2004;Kawamura, 2010;Maffione & Morris, 2017;Schumann, Stipp, Leiss, et al, 2014) or by analyzing crystallographic preferred orientations using diffraction techniques (e.g., Aplin et al, 2006;Day-Stirrat et al, 2012;Kopf & Behrmann, 1997;Schumann, Stipp, Leiss, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%